Estudo ambiental prévio da Barragem da Fonte do Mato do município de Caçapava do Sul – RS - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The population growth in Brazil usually occurs disorderly, which contributes to several problems due the inappropriate soil uses and human activities. Among these problems can be cited the pollution of water resources which is one cause of water scarcity. This impedes the complete water uses, including the ecological balance and human supply, being required to build water treatment stations. Therefore in this study was done a preliminary environmental study of the Fonte do Mato dam, including its tributary streams and the watershed in which the dam is located. These studies were done by verification of some water quality parameters and the delimitation of the permanent preservation areas (APP), risk areas and the region of the watershed, via remote sensing and geographic information systems. Were verified that the parameters color, pH and phosphorus in the dam were above the limits recommended by the Resolução CONAMA 357 and the emissions of domestic sewage was the principal source of pollution, 60% of the APP of the Fonte do Mato Stream was covered by riparian forest, however this value was sub estimated, was founded no APP regarded the altimetry of the watershed and most of the watershed was framed in class 2, moderate risk, due the lack of arboreal vegetation. Some considerations were done about the risks that the emissions of domestic sewage in the water sources can cause in human health and were proposed some later studies and solutions that can be done to improve the water quality and the conditions of the watershed.
Keywords: Poluição; Sensoriamento Remoto; APPs; Tratamento de Água; Uso e ocupação de solos; Pollution; Remote Sensing; Permanent Preservation Areas; Soil uses and occupation; Water Treatment; CNPQ::CIENCIAS EXATAS E DA TERRA